More in common (law) than originally thought? A theoretical first comparison of the Magna Carta and the Księga Elbląska - Higgins, J. Patrick (Acta Universitatis Lodziensis. Folia Iuridica, 2020)
Medieval legal scholars generally do not compare the Polish and English legal systems, though in the 13th century they share a surprising number of similarities. This is especially clear if one considers the convergent of evolution of legal institutions in response to socio-historical problems. This is concretely traced through historical and textual analysis of Magna Carta and Księga Elbląska, two foundational texts in their respective legal systems. Ramifications of this new comparative perspective are discussed, with avenues of further research outlined.